(untitled) (Muara Nada: Jurnal Pendidikan Seni, 2026)
This research examines the form of presentation of the traditional feko genda musical instrument in Ndungga Village, East Ende District, Ende Regency. This musical instrument is a cultural heritage consisting of feko (bamboo flute) and genda (drum). This research uses a qualitative approach with ethnographic methods. Data collection techniques include observation, interviews and documentation. The results of the research show that the8 presentation of Feko Genda’s music is in the form of an ensemble with a semicircle formation, played by six people in an open space at various traditional, entertainment and religious events. This form of presentation shows the existence of strong local cultural continuity. Feko genda’s music is not just an artistic expression, but also an identity and means of cultural communication for the Ndungga people. The unique presentation that is still sustainable today shows the community’s collective commitment to maintaining their ancestral cultural heritage, as well as the importance of regeneration to ensure the sustainability of this art in the future.